Occupational hazards: Perceptions of nurse managers at Intermediate Hospital Onandjokwe - Kristofina T. Nakatana; Hans Justus Amukugo; Salomo Salomo (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Managing occupational health hazards (OHH) in the nursing profession is crucial for improving nurses’ quality of life. Nurses are facing OHH while delivering patient care. These hazards can lead to morbidity, mortality and compromised patient care.